PERBANYAKAN VEGETATIF BIDARA UPAS (Merremia mammosa (Lour.) Hallier f) KEBUN RAYA BOGOR - Ria Cahyaningsih; Syamsul Hidayat; Endang Hidayat (Research Center for Biology-Indonesian Institute of Sciences, 2017)
Bidara upas (Merremia mammosa (Lour.) Hall.f.) is a medicinal plant, , that traditionaly use by Indonesian and Malaysian people. Regarding Indonesia Biodiversity Strategy and Action Plan released by The National Development Planning Agency, it is included in the extinct medicinal plant list (2003). As the center for plant conservation, Bogor botanical garden conducted vegetative propagation study on this plant by air layering, cutting, and tuber cutting. The aim to this study is to find effective for bidara upas which method is vegetative propagation. Air layering and cutting propagation modified by Rootone-F did not give any result, whereas tuber cutting propagation with GA3 gave positive result. Principally, propagation by tuber cutting modified by 50 ppm of GA3 dose gave the most rapid and highest uniformity on shoot emergence, the best on growing variables, namely average height of shoot growing, the number of secondary roots, the number and length of the primary roots. It cannot be concluded yet that propagation by tuber cutting modified by GA3 was the most effective. Hence, it is necessary to conduct another propagation studies of air layering and cuttings with more variants of treatments, especially Rootone-F dose.